3D connective micro-fragment enriched with stromal vascular fraction in osteoarthritis: chondroprotective evidence in a preclinical in vivo model - Desando, Giovanna; Tschon, Matilde; Martini, Lucia; Sartori, Maria; Giavaresi, Gianluca; Fini, Milena; Cellamare, Antonella; Soranzo, Carlo; Longinotti, Cristina; D’Alessandro, Martina; Roseti, Livia; Grigolo, Brunella (Frontiers in Cell and Developmental Biology, 2025)
IntroductionAdipose-derived cell therapies are one of the most common regenerative therapeutic options to alleviate the multi-component damage of osteoarthritis (OA). Adipose stromal vascular fraction (SVF) has gained scientific consensus for its ability to interact protectively with the joint microenvironment. Recently, the wide range of enzyme-free tissue processing systems has outperformed classical treatments, because of their ability to produce connective micrografts enriched with the SVF (mctSVF). This preclinical in vivo study evaluates the chondroprotective potential of a newly generated mctSVF compared with in vitro expanded adipose stromal cells (ASC) in OA.MethodsA mild grade of OA was induced through bilateral anterior cruciate ligament transection (ACLT) surgery in 32 Specific Pathogen Free (SPF) Crl: KBL (NZW) male rabbits followed by the surgical excision of inguinal adipose tissue. After 2 months, OA joints were treated with an intra-articular (IA) injection of mctSVF or ASC. Local biodistribution analysis was used to determine migration patterns of PKH26-labelled cells in the knee joint after 1 month. Efficacy was assessed by gross analysis, histology and immunohistochemistry on the osteochondral unit, synovial membrane and meniscus.ResultsWe elucidate the effectiveness of a one-step approach based on mechanical isolation of mctSVF. Through epifluorescence analysis, we found a similar pattern of cell distribution between cell treatments, mainly towards articular cartilage. Similar regenerative responses were observed in all experimental groups. These effects included: (i) osteochondral repair (promotion of typical anabolic markers and reduction of catabolic ones); (ii) reduction of synovial reactions (reduced synovial hypertrophy and inflammation, and change of macrophage phenotype to a more regenerative one); and (iii) reduction of degenerative changes in the meniscus (reduction of tears).DiscussionOur study demonstrates the validity of a novel mechanical system for the generation of the mctSVF micrograft with chondroprotective potential in a preclinical model of moderate OA. The resulting final product can counteract inflammatory processes beyond the OA microenvironment and protect cartilage through the colonization of its structure. The intact and active microanatomy of mctSVF makes it a suitable candidate for translational medicine to treat OA without the need for cell manipulation as with ASC.